Synthesis of PDMS containing block copolymers and their applications in oxygen sensing and pressure sensitive paints. (16th August 2021) - Shi, Jiayan; Wei, Chunhua; Shen, Min; Pan, Tingting; Tian, Yanqing
Abstract: Two new block copolymers (P1 and P2 ) containing platinum porphyrin-based phosphorescent probes with different molar ratios of polydimethylsiloxane (PDMS) and isobutyl methacrylate (IBM) were successfully synthesized via atom transfer radical polymerization (ATRP) with narrow polydispersity smaller than 1.21. For comparison, P3 without the PDMS block was also prepared. Results of 1 H NMR and GPC demonstrated their successful preparation. Oxygen sensing performance and pressure sensitivity of these polymers were investigated. Results showed that the polymer with more PDMS contents exhibited higher oxygen sensitivity, better pressure sensitivity, and faster response time. The pressure sensitivity of polymer with more PDMS contents was affected more significantly by temperature. The polymer P1 with a fraction of PDMS of 50 wt% reported herein showed a high pressure sensitivity of 0.82%/kPa, which is among the highest ones of the reported polymers. These results may provide helpful information for broadening the development of oxygen sensors and pressure sensitive paints. Graphical abstract: Image 1 Highlights: Atom transfer radical polymerization was used for synthesizing new pressure sensitive paints (PSP). The influence of PDMS on sensing performance was observed. The polymers exhibited high sensitivity to pressure.